Pengaruh Motivasi, Pelatihan dan Insentif Terhadap Kinerja Pegawai pada Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan Universitas Gadjah Mada - Nurviani Solichah; Zaenal Wafa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of motivation, training, and incentives on the performance of permanent education staff at the Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada (FK-KMK UGM). The approach used is quantitative with a survey method by distributing questionnaires to 257 respondents, and 148 data were obtained that were worthy of analysis. The independent variables in this study are motivation, training, and incentives, while the dependent variable is employee performance. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study indicate that motivation and training partially have a positive and significant effect on employee performance. However, incentives do not have a significant effect individually. However, simultaneously motivation, training, and incentives together have a significant effect on employee performance. This finding emphasizes the importance of integrated human resource management, with an emphasis on increasing motivation and effective training, as well as fair incentives to improve employee performance in supporting the